When Do Campaign Effects Persist for Years? Evidence from a Natural Experiment. Issue 4 (19th November 2019) - Jäger, Kai
Abstract: A unique revote allows for a natural experiment to evaluate whether campaign effects can last for nearly a decade: A right‐wing conservative party missed the 5% threshold in a German state by a mere vote in 2007, but the Constitutional Court ordered a revote in a single precinct over potential election fraud. After a one‐sided campaign focusing on law and order, the party's vote share increased more than sixfold. By comparing the precinct with its direct surroundings, the study shows that the revote campaign had long‐lasting effects on vote choice and broader security‐sensitive behavior. Residents in the revote precinct installed more warning signs on their property to deter burglars. They were not more supportive of right‐wing attitudes but were more likely to believe that election fraud reoccurred. Based on habitual‐voting and social‐norm theories, the study suggests that persuasion could be durable if candidates provide an unchallenged interpretation of political events.